Исследования скифского царского Александропольского кургана в 2009 г. - Полин, С.В. (Археологічні дослідження в Україні, 2010)
The Scythian Steppe Expedition of the IA NASU continued a research of the Scythian royal Olexandrivskyi barrow near Petrykivka village of Dnipropetrovsk Oblast. The Central tomb was opened for the second time, and its planning and size were specified. Existence of three bays in the side walls was determined, while existence of arch-like robbers’ passages in virgin soil along the lengthwise walls of the catacomb was not confirmed. Rare finds by their composition in general agree with the finds from excavations in the 19th c.; however several new types of stamped plates and beads were discovered. Also, the research of traces of funeral feast near the barrow was continued. On the territory of about 300 m2 in the south-western section of the barrow animal bones, several amphorae fragments, and two heaps of rocks were found. In total, about 370 amphorae and 53 amphorae stamps were found in remains of funeral feast.